CHRYSANTHEMUM MORIFOLIUM FLAVONE AGLYCON EXTRACTION METHOD, EXTRACT OBTAINED BY THE SAME, AND ANTI INFLAMMATORY PHARMACEUTICAL COMPOSITION - LU CHU-HSUN; CHEN WEN-YIN; YANG TSUNG-LIN; CHEN YU-WEN; ANGELA GOH; YAO HSIN-JAN; PAN I-HONG (2023)
To provide a method for extracting flavone aglycon such as luteolin and apigenin in Chrysanthemum morifolium.SOLUTION: There is provided a method comprising: (a) a step for immersing a Chrysanthemum morifolium raw material in water or solution, performing an immersion step for 3.5 hours or more, for acquiring an immersed sample; (b) a step for adding an extraction solvent to the immersed sample, performing an extraction step for 5-60 minutes for acquiring the extract. In the Chrysanthemum morifolium, at least one of following portions of the Chrysanthemum morifolium, namely, a whole plant, root, stem, leaf and a flower.SELECTED DRAWING: None 【課題】イエギク中のルテオリン、アピゲニン等のフラボンアグリコンを抽出する方法を提供する。【解決手段】方法は、（ａ）イエギク原料を水または水溶液中に浸し、浸漬工程を３．５時間以上行って浸漬試料を得るステップと、（ｂ）抽出溶媒を浸漬試料中に加え、抽出工程を５～６０分行って抽出液を得るステップとを含む。イエギク原料には、イエギクの下記する部位、つまり全草、根、茎、葉および花のうちの少なくとも１つが含まれる。【選択図】なし